Tinjauan Literatur: Evaluasi Pelaksanaan Program GERMAS Nasional - Putri Anggraeni, Ela; Putriyanti, C. Ermayani; Jaelan (Jurnal Kesehatan, 2024)
GERMAS (Community Movement for Healthy Living) is a program organized by the Ministry of Health that aims to improve the quality of life. GERMAS invites the community to cultivate healthy living to change unhealthy habits or behaviours. However, public awareness of the importance of a healthy lifestyle is still lacking in its implementation. The problem regarding the implementation of GERMAS occurs in some parts of Indonesia. Many people do not understand the negative impacts of unhealthy habits and do not have the motivation to change their behaviour. This research aims to know the extent to which the GERMAS program is implemented in Indonesia and provide an evaluation of the program's implementation. This research is a literature study that analyses and reviews previous research. The databases used were Garuda and Google Scholar database, using the keywords GERMAS evaluation, GERMAS program, and GERMAS implementation. This review applies restrictions on the year of publication, namely from 2019 to 2023. Ten articles met the criteria. Results of the study showed that there are still obstacles based on the evaluation of the GERMAS implementation program in Indonesia. Therefore, the government needs to monitor, evaluate, and take action to overcome obstacles to the implementation of the GERMAS program in order to increase the effectiveness of the GERMAS program in clean and healthy living behaviour in the community in Indonesia.